1998
DOI: 10.1007/s002130050607
|View full text |Cite
|
Sign up to set email alerts
|

N -Methyl- D -aspartate receptors in the nucleus accumbens⋅are involved in detection of spatial novelty in mice

Abstract: The aim of this study was to investigate the role played by intra-accumbens N-methyl-D-aspartate (NMDA) receptors in spatial information encoding. For this purpose, the effect of local administration of both competitive (AP-5) and non-competitive (MK-801) NMDA antagonists was assessed in a task designed to estimate the ability of rodents to encode spatial relationships between discrete stimuli. The task consists of placing mice in an open field containing five objects and, after three sessions of habituation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 48 publications
3
37
0
Order By: Relevance
“…In particular, there is evidence of a possible role of the ventral striatum in processing spatial information (Annett et al, 1989;Seamans and Phillips, 1994;Maldonado-Irizarry and Kelley, 1995;Floresco et al, 1996Floresco et al, , 1997Roullet et al, 1997;Usiello et al, 1998). This hypothesis is sustained by neuroanatomical data that show dense projections to the Nacc from structures involved in spatial learning, such as the hippocampus, the prefrontal cortex, and the entorhinal cortex (Beckstead, 1979;Kelley and Domesick, 1982;Groenewegen et al, 1987).…”
mentioning
confidence: 60%
“…In particular, there is evidence of a possible role of the ventral striatum in processing spatial information (Annett et al, 1989;Seamans and Phillips, 1994;Maldonado-Irizarry and Kelley, 1995;Floresco et al, 1996Floresco et al, , 1997Roullet et al, 1997;Usiello et al, 1998). This hypothesis is sustained by neuroanatomical data that show dense projections to the Nacc from structures involved in spatial learning, such as the hippocampus, the prefrontal cortex, and the entorhinal cortex (Beckstead, 1979;Kelley and Domesick, 1982;Groenewegen et al, 1987).…”
mentioning
confidence: 60%
“…Several authors have previously indicated an important role of Nacc in learning and memory processes (Annett et al 1989;Maldonado-Irizarry and Kelley 1995;Usiello et al 1998). However, most of these studies used pretraining pharmacological or lesion treatments that do not allow distinguishing between the different phases of learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, intact transmission from cortical and allocortical brain areas seems to be essential for correct processing of spatial information (Floresco et al 1997;Sargolini et al 1999). Along this line, it has been demonstrated that blockade of both classes of glutamate receptors within the Nacc impaired performance in different spatial learning tasks (MaldonadoIrizarry and Kelley 1995; Usiello et al 1998). However, in these studies pretraining pharmacological manipulations have been used; therefore, it is difficult to dissociate the effects on the different phases of information processing.…”
mentioning
confidence: 99%
“…This form of learning appears to require expression of neurotrophins (Calamandrei et al, 2002;Niewiadomska et al, 2006) and exercise-induced enhancement of task performance has been associated with increases in hippocampal and perirhinal BDNF (Griffin et al, 2009). Furthermore, successful performance of the task is dependent on glutamatergic signalling through NMDA (Roullet et al, 1996;Usiello et al, 1998;Larkin et al, 2008) and AMPA receptors (Roullet et al, 2001). A dopaminergic component has also been identified (Roullet et al, 1996;Mele et al, 2004) and interactions between these glutamate and dopamine systems in the nucleus accumbens have been implicated in the consolidation of this task (Ferretti et al, 2005).…”
Section: The Role Of the Perirhinal Cortex In Context And Spatial Memorymentioning
confidence: 99%